AGILE SCRUM-BASED DOCUMENT MANAGEMENT SYSTEM DENGAN ROLE-BASED WORKFLOW UNTUK INDUSTRI MANUFAKTUR: AGILE SCRUM-BASED DOCUMENT MANAGEMENT SYSTEM WITH ROLE-BASED WORKFLOW FOR MANUFACTURING INDUSTRY - Fachrur Rizhky Al Fadillah; Hafiyyan Putra Pratama (LPPM Universitas Abdurrab, 2026)
Digital transformation in document management has become a crucial urgency to enhance efficiency and reduce reliance on physical documents. In the manufacturing sector, paper-based manual processes frequently trigger operational bottlenecks, such as sluggish approval bureaucracies, complex archive retrieval, and material waste. In response to these challenges, this study aims to design and implement a web-based Document Management System (DMS) equipped with an integrated role-based workflow mechanism. The system development approach adopted the Agile Software Development methodology using Scrum to ensure adaptive iterations throughout each sprint. Technically, the architecture was built using the Next.js framework with a PostgreSQL database and securely deployed within the company's intranet network. Testing results demonstrated a highly positive quantitative impact. The document approval cycle was successfully reduced from an average of six working days to just one day, representing an 83% surge in efficiency. Furthermore, the consumption of physical materials such as paper and toner was reduced by over 90%. The system also massively accelerated archive retrieval time, dropping from 10–30 minutes to a mere 1–3 seconds. In conclusion, the implementation of this digital DMS is proven to be vital in driving operational efficiency and realizing a paperless work ecosystem.